Analysis of the Effectiveness and Contribution of Land and Building Tax, and Land and Building Acquisition, Duty on Local Revenue in the City of Bandung Before and During the Covid-19 Pandemic - Risdiana, Seviani; Suratminingsih, Suratminingsih; Evianti, Dessy; Arum, Mega (Maksi, 2023)
This study aims to determine the effectiveness level of the Land and Building Tax (PBB) and Land and Building Acquisition Fee revenues (BPHTB), as well as the contribution of PBB to the Local Revenue (PAD). With the enactment of Law No. 28 of 2009 on Local Taxes and Regional Levies, the authority for collecting Local Taxes is fully implemented by the Regional Government. As a result, PBB and BPHTB, which were previously classified as Central Taxes, have now become Local Taxes. This study utilizes a quantitative research method with a descriptive research approach. The findings indicate that the PBB of revenues in the City of Bandung over the past four years from 2018 to 2021 showed an initial increase followed by a decline, resulting in varying criteria. Similarly, the PBB of the Land and Building Acquisition Fee revenues in the City of Bandung during the same period exhibited a decreasing trend, leading to a decrease in the effectiveness level from "sufficiently effective" to "ineffective". Furthermore, the PAD in the City of Bandung experienced a decline from 2018 to 2019, followed by an increase from 2019 to 2020, and a significant decrease from 2020 to 2021. DOI: https://doi.org/10.32897/ajib.2023.2.1.2828